INTERNATIONALIZATION OF MUHAMMADIYAH EDUCATION:: A STUDY OF MUHAMMADIYAH AUSTRALIA COLLEGE - Qori, Mudrik; Romelah, Romelah; Nurhakim, Moh. (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article aims to analyze the objectives, functions, and management of the Muhammadiyah Australia College (MAC) program in Australia. In the research process, the researcher uses a qualitative approach with a type of library research. Data and information collection is conducted through documentation techniques, while data analysis is carried out using content analysis techniques. From this research, it can be concluded that: (1) there are four main objectives of the MAC program, which are: to become a center of education that embodies rahmatan lil alamin (a blessing for all creation), to educate students with Islamic spiritual values and local cultural values, to shape students into tolerant and law-abiding individuals, and to foster students to become competent global citizens; (2) there are four main functions performed by MAC, which are: contributing positively to local communities, providing opportunities for Indonesians who wish to study in Australia, serving as a place for student exchange programs, and promoting the principles and practices of Australian democracy; and (3) MAC's management is guided by two main principles: all activities must align with MAC's vision, mission, objectives, and core values, and a commitment to child safety.